Implementasi Pengelolaan Zakat Profesi Aparatur Sipil Negara Kementerian Agama Kabupaten Demak - Siti Mualimah; Edi Kuswanto (IAIN Salatiga, 2019)
This study aimed at determining the implementation of professional zakat for the State Civil Apparatus (ASN), especially in the Ministry of Religius Affairs of Demak Regency. The study used a descriptive qualitative approach. The results showed that the management of professional zakat in the Ministry of Religius Affairs of Demak Regency was the joint responsibility of the Zakat Collector Unit of the Ministry of Religius Affairs of Demak Regency and the BAZNAS of Demak Regency. The Zakat Collector Unit of the Ministry of Religius Affairs of Demak Regency manages 75% of theprofessional zakat collected while the remaining 25% is managed by the BAZNAS of Demak Regency. Whereas the istribution of professional zakat is intended for 8 Ashnaf who are entitled to receive according to Islamic sharia in two forms, namely zakat for consumption and zakat is productive. Zakat profession of the State Civil Apparatus Ministry of eligius Affairs Demak Regency is taken from the gross basic salary of each employee with a level of 2.5%, while the deduction is carried out by the treasurer of salaries based on the statement made